Parmeliaceae (fungos liquenizados) em três áreas da Amazônia Mato-Grossense, Brasil - Ciecoski, Fabiana Aparecida Rego (2022)
The Amazon stands out for having the greatest biodiversity on the planet, being this natural heritage of immense economic and environmental value. However, activities linked to the exploitation of its natural resources, such as the increasing deforestation, for example, confirm that important information about different biological groups is neglected, as is the case of lichenized fungi. This work aimed to expand the knowledge about lichenized fungi of the family Parmeliaceae in the Amazon of Mato Grosso state. The collections were carried out in three study areas: the Cristalino State Park, the Xingu State Park, and the Fazenda São Nicolau. Samples of lichenized fungi were collected with aid of a knife and hammer from in random displacement at 30 points distributed in the study areas. The samples were individually packed in paper bags and sent to the Acervo Biológico da Amazônia Meridional, where they were viewed a stereomicroscope and optical microscope, in order to visualize structures of taxonomic importance and proceed with the identification at the genus level. Taxa were identified at the species level in Dr. Marcelo P. Marcelli’s laboratory (IML) located in São Roque city (São Paulo state) through detailed morphological analysis, complementary chemical tests, thin layer chromatography and microcrystallization. Altogether 71 samples of lichenized foliose fungi of the Parmeliaceae were analyzed, resulting in 39 species belonging to 5 genera: Bulbothrix, Parmelinella, Parmotrema, Pseudoparmelia and Canoparmelia. Of those, 3 species are new records for Mato Grosso State and 34 are new species for science. The species were described under the latest version of the Protocol of the Lichenological Studies Group (GEL) of the Instituto de Pesquisas Ambientais developed by Dr. Marcelli (added with anatomical particularities present in Amazonian specimens) and prepared for 5 different publications observing chemical groups and the genus of the species. This research concluded that in the three studied areas the occurrence of lichens was more abundant in more illuminated places with an open canopy, and that the large number of new species found characterizes the study areas as reservoirs of biodiversity that are in need of further studies on this and other families. Parmotrema was the most representative genus with a total of 33 species of which 30 are new species, followed by Bulbothrix with three species of which two are new, and Canoparmelia, Pseudoparmelia and Parmelinella, each of them with one new species. This study can also support public environmental policies aimed at the conservation of the Amazon biome.